KARAKTERISTIK KWETIAU YANG DITAMBAH TEPUNG TAPIOKA DAN RUMPUT LAUT Gracilaria gigas HARVEY - Hardoko, Hardoko; Saputra, Tefvina Irma; Anugrahati, Nuri Arum (Fakultas Perikanan dan Kelautan Universitas Riau, 2013)
Gracilaria gigas, an edible seaweed was used as gelling agent. The objective ofthis study were to observe the effect of Gracilaria gigas addition as flat rice noodles’gelling agent. The experimental method was conducted to determine the bestconcentration of tapioca and concentration of Glacilaria powder (0%, 5%, 10%,15%,20%, 25%, and 30% based on total rice and tapioca flour weight) of flat rice noodlecharacteristic. The result showed that the best flat rice noodles made from 28.6% IR 64rice flour, 20% tapioca starch addition (based on rice flour weight), and 20% seaweedflour addition (based on total rice and tapioca flour weight). The addition of 20%seaweed flour (based on total rice and tapioca flour weight) on flat rice noodle gave thebest organoleptic acceptance and greater chewiness than others.